Phase I studies: a test bench for Italian clinical research. Issue 4 (August 2020) - Cagnazzo, Celeste; Nanni, Oriana; Arizio, Francesca; Franchina, Veronica; Cenna, Rosita; Tabaro, Gianna; Vannini, Francesca; Procopio, Giuseppe; Gori, Stefania; Di Costanzo, Alessandro
Background: The Agenzia Italiana del Farmaco (AIFA) Determination 809/2015 sets all the requirements that clinical units and laboratories must meet in order to conduct phase I studies. Requirements include buildings, equipment, personnel, emergency management, as well as quality requirements defined in a set of standard operating procedures. Methods: In September 2018, the Italian Association of Medical Oncology working group, Clinical Research Coordinator, created an anonymous survey addressed to 51 medical directors of oncologic/hematologic clinical phase I units and all medical directors of generic and transversal units located in Italy and listed at the AIFA website. Results: Questionnaires from 24 institutions were collected, 9 previously inspected by competent authorities. All surveyed structures are certified to conduct profit studies and 1 is authorized to include healthy volunteers; 15 units implemented a Clinical Trial Quality Team in order to conduct nonprofit studies. At the time of data collection, a total of 398 proposals for phase I trials have been received, more than 50% coming from 3 institutes. A total of 144 phase I studies were active, with a median of 2.5 (Q1–Q3=0–6) studies for each center and asymmetric distribution of proposals. Conclusion: The considerable number of proposals received from the interviewed centers indicates that Italy plays an important role in the international pharmaceutical scene, despite bureaucratic procedures that threaten exclusion from decision-making. The AIFA Determination will be an important opportunity to acquire a competitive working approach.